Blue Light Photobiomodulation as treatment for peristomal skin disorders: case series - Stefano Gasperini; Mario Antonini (Infermieristica Journal)
Introduction. Keeping the peristomal skin intact proves to be a challenge for stoma patients and the health care teams that work with them. Peristomal skin complications are shown to affect 36.3% to 73.4% of patients. They are often particularly difficult to treat with topical therapies since the topical medications available are cream-based or ointment type formulations that don’t allow for perfect adhesion of the pouching system to the abdomen’s skin. In this study a preliminary evaluation of the effectiveness of Blue Light Photobiomodulation in the treatment of peristomal skin disorders was performed